Update of Diagnostic and Treatment of Trigeminal Neuralgia - Chumpitaz Cerrate, Víctor (2013)
Trigeminal neuralgia (TN) is a painful neuropathic condition that involves one or more branches of the trigeminal nerve. The pain produced for the TN is described as a very intense acute pain, stabbing or shooting, as an electric shock that usually occurs of form unilateral and that goes all the way of the nerve involved. It is important to make the opportune diagnosis of the condition of TN for adequately differentiate of some odontogenic painful conditions and to prevent that the patient receive unnecessary treatment. The first line of treatment of the TN is the pharmacological therapy, in which is used as a drug of first choice to carbamazepine. The second line of treatment of TN is the non-pharmacological therapy, where include various options of surgical treatment: etiologic or symptomatic.